Exosomes Mediate APP Dysregulation via APP-miR-185-5p Axis - Ding, Lu; Yang, Xiaoyu; Xia, Xiaohuan; Li, Yunxia; Wang, Yi; Li, Chunhong; Sun, Yiyan; Gao, Ge; Zhao, Shu; Sheng, Shiyang; Liu, Jianhui; Zheng, Jialin C. (Frontiers in Cell and Developmental Biology, 2022)
APP misexpression plays a crucial role in triggering a complex pathological cascade, leading to Alzheimer’s disease (AD). But how the expression of APP is regulated in pathological conditions remains poorly understood. In this study, we found that the exosomes isolated from AD mouse brain promoted APP expression in neuronal N2a cells. Moreover, exosomes derived from in N2a cells with ectopic expression of APP (APP-EXO) also induced APP dysregulation in normal N2a cells. Surprisingly, the effects of APP-EXO on APP expression in recipient cells were not mediated by the direct transferring of APP gene products. Instead, the effects of APP-EXO were highly likely mediated by the reduction of the expression levels of exosomal miR-185-5p. We found that the 3’UTR of APP transcripts binds to miR-185-5p, therefore inhibiting the sorting of miR-185-5p to exosomes. N2a cell-derived exosomes with less amount of miR-185-5p exert similar roles in APP expression to APP-EXO. Lastly, we demonstrated a significant decline of serum exosomal miR-185-5p in AD patients and AD mice, versus the corresponding controls. Together, our results demonstrate a novel mechanism in the exosome-dependent regulation of APP, implying exosomes and their miRNAs as potential therapeutic targets in treating AD and biomarkers for AD diagnosis.